Radiographic evaluation of the S2-complex drug on the alveolar bone height (Mustansiria Dental Journal, 2024)
The S2-complex drug is a chemical preparation of a low molecular weightsynthetic organometalic complex, and it has experimented in many researches to proveit’s activity in the treatment of the cancerous tumors, without any side effects. This drugis a potent immunomodulat or that stimulates both, the humoral a.nd cell mediated,immune responsesTo examine the effect of S2—complex administered locally and was designed totest the potential effectiveness of S2-complex in the management of periodontal disease.associated bone loss by radiographic evaluationThirty six pairs of similarly involved periodontal pockets in (20) patients agedbetween (30-50) years old with pocket depth more than 6 mm were selected. Split mouth,randomized study was carried out. Scaling and root planing was carried out in both sidesin test side received S2- complex for five days in a daily dose of O.l mm/kg injecteddeeply until reaching the bone of affected site, while the control side was received distalwater for 5 days in a daily dose of 0.l mm/kg injected in the same way as that for testside. S2 complex was infiltrated locally through the gingival tissue of the effected site.deeply until reach the defect bone using disposable insulin syringesClinical attachment level of gingiva were recorded at baseline and repeatedonce every 2 weeks. Periapical radiographs were taken for both test and control sides atbaseline and at the termination of the treatment after 2 months. A long the time of study,the patients put on a program of motivation to keep a good stander of oral hygieneClinical and radiographical parameters in general showed improvement with both test.and control groups, with a statical significant difference between themRadiographical evaluation showed high differences in hight and density of bone forboth groups, and effect to S2-complex was on sites of anterior and molar areas according